A Literature Review on Coaching Methods for Tutoring Students in Undergraduate Education - Guillem Villa; José Antonio Montero; Xavier Solé-Beteta; Joan Navarro (MDPI AG, 2024)
Recently, the integration of coaching methodologies within educational environments has garnered significant attention due to their potential to enhance student learning outcomes and overall academic performance. While the literature extensively examines the effectiveness of coaching in a plethora of scenarios (e.g., sports, business, and entrepreneurship), there remains a notable research gap regarding its application within undergraduate educational environments, where coachees have unique characteristics in terms of background, age/maturity, resources availability, and population size. This literature review aims to address this gap by synthesizing existing research on the implementation of coaching strategies in educational settings and how they can cope with a large number of students. Through a comprehensive analysis, this study elucidates the current state of knowledge, identifies prevailing methodologies, and evaluates the outcomes associated with employing coaching techniques in group contexts. Moreover, this work explores the potential benefits and challenges of utilizing coaching strategies in group sessions, offering insights into their scalability and applicability within diverse educational settings. The findings of this review underscore the importance of further research in this domain to advance our understanding of how coaching methodologies can be effectively adapted to facilitate collaborative learning experiences and promote student success on a broader scale. Ultimately, this study advocates for the integration of group coaching approaches as a promising avenue for enhancing the efficiency and accessibility of traditional tutoring and mentoring practices in education.